The Tide Raising all Boats? Social Class Differences in Political Participation among Young People in Scotland. Issue 2 (May 2022) - Huebner, Christine; Eichhorn, Jan
Abstract : Social class differences in political participation are a pressing issue for democracies and they are particularly severe among young people in the UK. Disadvantaged young people are the least likely to be politically engaged in the UK and it is assumed that with declining levels of participation inequalities in political participation increase. What happens to political inequality though when levels of youth participation increase ? Do more advantaged young people account for most of the extra participation or do disadvantaged young people 'catch up'? Based on representative survey data, this paper investigates levels of political inequality among 16- and 17-year-olds in a context of increasing participation in Scotland. We find that in Scotland young people of all social classes were equally likely to be politically engaged, while among young people in the rest of the UK and adults from Scotland those of higher social status were more likely to be engaged in politics. Overall, social class differences in political engagement were less pronounced amongst 16- and 17-year-olds in Scotland than in the rest of the UK. The paper offers some possible explanations of this finding and suggestions for further research.